2007
DOI: 10.1080/15397730701617814
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Orthotropic Materials on the Vibration Characteristics of Structural Systems#

Abstract: The rapid growth in anisotropic material (such as composite materials) usage marks a new era in material science. Obviously, in order to understand the physical behavior of structural systems constituted by composite materials, several parameters, such as natural frequencies, mode shapes, and transmissiblities, must be incorporated into anisotropic elastic analyses. Orthotropy, as a special case of anisotropy, is common in almost all fields of civil and mechanical engineering. The objective of this effort is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The method with implementation of an interlacing grid technique which is about vibrating plate problems was examined by Aksu and Felemban (1992) and Aksu and Al-Kaabi (1987). Using a similar technique, free and forced vibration analysis of viscoelastically supported plates was investigated by Kocatu¨rk and Altintas ( 2003), Altintas andBagci (2004, 2005), Altintas and Goktepe (2007) and Altintas (2009). The numerical method based on VDM by which the analyses have been applied in this study is described briefly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method with implementation of an interlacing grid technique which is about vibrating plate problems was examined by Aksu and Felemban (1992) and Aksu and Al-Kaabi (1987). Using a similar technique, free and forced vibration analysis of viscoelastically supported plates was investigated by Kocatu¨rk and Altintas ( 2003), Altintas andBagci (2004, 2005), Altintas and Goktepe (2007) and Altintas (2009). The numerical method based on VDM by which the analyses have been applied in this study is described briefly.…”
Section: Methodsmentioning
confidence: 99%
“…In the three particular cases studied by Wong (2002), it was reported that the added mass would reduce the amplitude of an antinode close to it and all vibration antinodes around the added mass would appear to be shifted towards the loaded region. Altintas and Goktepe (2007) studied free vibration analysis for the location of mass and forced vibration analysis for both the location of mass and force. The findings of the free vibration part of that study support those of Wong's (2002) study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural damping also decreases due to the lack of vibration-absorbing materials. Moreover, these kinds of frameworks usually employ orthotropic materials, whose dynamic behavior varies significantly from isotropic ones [1]. All these factors can produce an inappropriate vibration response to daily activity loads, i.e., human walking forces, machinery, etc.…”
Section: Introductionmentioning
confidence: 99%